The complete Elfquest. Volume two - Pini, Wendy; Pini, Richard (Dark Horse Books, 2015)
"The elves have reclaimed the Palace of the High Ones, but it is not the safe haven they believed. New threats loom as Winnowill, lord of Blue Mountain, vows to destroy all trace of the Wolfriders, and Cutter's rival Rayek is overcome with power"--